The long shadow of Versailles: An unusual controversy on John Maynard Keynes between the German ordoliberals Walter Eucken and Wilhelm Röpke - Karen Horn (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2023)
Ordoliberalism and Keynesianism are not exactly known to fit hand in glove. Accordingly, the German economists Walter Eucken, head of the Freiburg school, and Wilhelm Röpke, from his Istanbul and Geneva exiles, were in near perfect agreement in their opposition to the interventionist "full employment" teachings of their English colleague John Maynard Keynes. An article by Röpke on Keynes in the Swiss newspaper Neue Zürcher Zeitung (NZZ) published in 1946 however met with "fundamental objections" by Eucken, and a controversy took off. The bone of contention between the two colleagues and rather dissimilar friends was Keynes's famous earlier critique of the Versailles Peace Treaty, and the lessons to be drawn for the post-WW II situation. This paper tells the story of this unusual and puzzling controversy, quoting from the letters between the two, and contextualizes the exchange in order to make sense of it. It turns out that there was an economic, a human, and - most significantly - a political side to their disagreement. Eucken and Röpke assessed the economic development since 1919 somewhat differently, and Eucken felt compelled to defend Keynes against the heavy moral accusation of having contributed to the Nazi catastrophe. But perhaps most of all, he found it tactically unwise in 1946 to endorse arguments that would support an even harsher attitude by the Allies toward Germany after WW II. In a first translation, the paper's appendixes contain Röpke's NZZ article that sparked the controversy, as well as the rejoinder by Eucken's former student Valentin F. Wagner. A new, full translation of an earlier NZZ article by Röpke on Keynes in lieu of an obituary is also provided.
Keywords: B20; B31; N14; 330; Eucken; Röpke; Keynes; Versailles Peace Treaty; reparations; full employment policy